Green Purchase Intention among Generation Z Consumers: Does Green Trust Still Matter? - Naufal Rochman; Dewi Deniaty Sholihah (Jurnal Ekonomi, Manajemen, dan Bisnis, 2026)
The increasing pollution caused by plastic waste, along with the rise of the green consumerism trend, has encouraged businesses to develop more environmentally friendly products by targeting the Generation Z consumer segment. However, the high awareness of environmental issues is not necessarily reflected in consistent green product purchasing behavior among consumers. This research set out to assess how far green perceived value, environmental concern, and green trust shape the green purchase intention of Generation Z consumers of Eiger tumbler products in Surabaya. A quantitative survey design was used, drawing on a purposive sample of 160 participants, with data gathered via an online questionnaire and processed through PLS-SEM in SmartPLS. Results show that both green perceived value and environmental concern exert a positive and meaningful effect on green trust as well as on green purchase intention. By contrast, green trust did not significantly affect purchase intention and was unable to mediate the relationship between the two predictor variables and purchase intention. These outcomes suggest that Generation Z places greater weight on a product's tangible benefits and their own environmental commitment than on confidence in a brand's sustainability claims. The study further contributes to the body of knowledge on green consumer behavior, particularly regarding locally produced reusable goods within developing country markets.